Modele mieszanek w taksonomii i regresji - graficzna prezentacja wyników - Witek, Ewa (Mixture Models in Clustering and Regression - Graphical Results, 2009)
The paper focuses on finite mixture models and their application in clustering and regression. These models are often used to capture overdispersion in the data which can occur for example if important covariates are omitted in the regression. It is then assumed that the influence of these covariates can be captured by allowing a random distribution for the intercept. The author presents the graphical results of research.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 124-132